Design a Switchable Band Notch Π-Slot Reconfigurable Antenna for Ultra Wide Band Applications (مجلة المنصور, 2022)
Square patch frequency and radiation reconfigurable microstrip antenna design is proposed for Ultra Wide Band application. The notch band function was created by embedding a Π-slot within the radiator patch that has a small size (24 × 23) mm printed over a FR-4 substrate with relative dielectric constant of 4.3, and thickness of 1 mm. A microstrip line feeds the designed antenna. To satisfy the UWB frequencies the length ground plane has been reduced. The finite ground plane is printed on the lower side of dielectric substrate. The simulating process and performance estimation of the designed antenna was achieved by using the electromagnetic simulator, Computer Simulation Technology Software. Simulation results indicate that the designed antenna has an effective bandwidth, for |S_11 |≤-10 dB, extending from approximately (3.7 to 8) GHz and (8.8 to 10.75 GHz), with a switchable notch band performance in the (5.15 and 5.825 GHz).